Downregulation of MAPK/MAK/MRK overlapping kinase 1 in peripheral blood mononuclear cells of pediatric patients with type 1 diabetes mellitus - Sopić, Miron; Ninić, Ana; Ostanek, Barbara; Bojanin, Dragana; Milenković, Tatjana; Munjas, Jelena; Mihajlović, Marija; Vekić, Jelena; Marc, Janja; Spasojević-Kalimanovska, Vesna (Journal of Medical Biochemistry, 2021)
Background:Type 1 diabetes mellitus (T1DM) is one of the most common endocrine diseases in children. T-cell autoreactivity toward β-cells is controlled by significant changes in metabolism of T cells. Mammalian target of rapamycin (mTOR) is an important intracellular regulator of metabolism and cell growth. MAPK/MAK/MRK overlapping kinase 1 (MOK1) is one of the less known regulators of mTOR. We sought to investigate if MOK1 and mTOR mRNA levels in peripheral blood mononuclear cells (PBMCs) of T1DM pediatric patients are different compared to healthy subjects.Methods:This study included 172 adolescents with T1DM and 36 healthy adolescent volunteers designated for control group (CG). MOK1 and mTOR mRNA levels were determined in PBMCs by qPCR.Results:T1DM patients have significant downregulation of MOK1 mRNA levels in PBMCs compared CG (P=0.018), while there was no significant difference in mTOR mRNA levels (P=0.891). Furthermore, in T1DM patients, MOK1 significantly correlated with age, BMI, triglycerides and mTOR, while mTOR correlated significantly with BMI and systolic blood pressure. Overweight T1DM subjects had significantly lower MOK1 (P=0.034) and mTOR (P=0.017) mRNA levels, together with significantly higher levels of systolic blood pressure (P
Keywords: type 1 diabetes mellitus; Mammalian target of rapamycin; MAPK/MAK/MRK overlapping kinase 1